Increasing Jatam Kroya’s Agricultural Production by Creating “Boosters” from the Environment - Wakhudin, Wakhudin; Wijanarko, Beny R; Purbomartono, Cahyono (Society : Jurnal Pengabdian Masyarakat, 2025)
This community service (IbM) aims to increase agricultural production in the community that is part of the Muhammadiyah Farmers Association (Jatam) in Kroya District, Cilacap Regency, Central Java by making "Boosters" from various natural resources. This effort is a solution to the increasing cost of chemical agricultural drugs that can have an impact on environmental pollution, which in turn can be harmful to humans. This community service method uses a participatory-educational method, through a direct educational approach, practical training, and mentoring. The community service team visits a number of farmers' gardens and rice fields, provides extension services by inviting agricultural experts from universities, monitoring, and evaluation at any time carried out through the WhatsApp Group. The community service team in this case provides extension on how to make Boosters from materials available in the surrounding environment, in the form of: Root and vegetative growth boosters; Flowering and fruit boosters; Disease resistance boosters; and soil fertility boosters. A sign that fermentation is successful is, a sour or sweet aroma, no foul odor. If moldy, add 2 tablespoons of sugar to activate good microbes.